Heart rate variability: a tool to explore the sleeping brain? - Chouchou, Florian; Desseilles, Martin (Frontiers in Neuroscience, 2014)
Sleep is divided into two main sleep stages: 1) non-rapid eye movement sleep (non-REMS), characterized among others by reduced global brain activity; and 2) rapid eye movement sleep (REMS), characterized by global brain activity similar to that of wakefulness. Results of heart rate variability (HRV) analysis, which is widely used to explore autonomic modulation, have revealed higher parasympathetic tone during normal non-REMS and a shift toward sympathetic predominance during normal REMS. Moreover, HRV analysis combined with brain imaging has identified close connectivity between autonomic cardiac modulation and activity in brain areas such as the amygdala and insular cortex during REMS, but no connectivity between brain and cardiac activity during non-REMS. There is also some evidence for an association between HRV and dream intensity and emotionality. Following some technical considerations, this review addresses how brain activity during sleep contributes to changes in autonomic cardiac activity, organized into three parts: 1) the knowledge on autonomic cardiac control, 2) differences in brain and autonomic activity between non-REMS and REMS, and 3) the potential of HRV analysis to explore the sleeping brain, and the implications for psychiatric disorders.